Defensoria pública como expressão e instrumento do regime democrático e a densificação do conceito jurídico de necessitado - Marcelo Paes Ferreira da Silva (2016)
This work deals with access to justice in view of the public service of legal assistance provided by the Public Defender´s Office as an expression of the democratic regime. Challenging the traditional and reductionist conceptions of the concept and scope of legal aid phenomenon, it intends to demonstrate that the Public Defender's Office, constitutionally dedicated institution to ensure the access of millions of Brazilians to fair legal system, experienced a historical process of building and shaping their identity. In this sense, it is claimed the mistake of the traditional view, linked to the liberal paradigm, which includes the Public Defender's Office as an organ of the state bureaucracy intended, solely and exclusively, to ensure access of the poor to the courts. Other hand, consolidates a contemporary vision of the institution, punctuated by the expansion of its performance space. Thus, it is argued that the Public Defender´s Office in the Democratic State of Law is presented as a real social counter-power, a constitutional guarantee against majority that seeks to improve the democratic system through social inclusion and the construction of citizenship.